My haunted house - Sage, Angie; Pickering, Jimmy; Bloomsbury (London : Bloomsbury, 2006)
Araminta enlists the help of several ghosts in an attempt to stop her Aunt Tabby from selling Spook House.
6.1
3-6
Keywords: Family -- Juvenile fiction; Ghosts -- Juvenile fiction; Haunted houses -- Juvenile fiction; Family life -- Fiction; Ghosts -- Fiction; Haunted houses -- Fiction; Ghost stories